Attack side and direction during the 2017 Judo World Championship - Guedes de Camargo, R.; Magalhães Guerra, G.; Rosa, R. L.; Calmet, M.; Takito, M. Y.; Franchini, E. (Sport Sciences for Health, 2019)
During competitions, one of the main goals of judo athletes is to throw their opponents onto their backs, with force and control, to score an ippon, which ends the match [1]. To create the opportunity to apply a throwing technique, judo athletes need to go through the displacement without contact and gripping phases [1]. The judo throwing technique is classically divided in three main phases [2]: (a) kuzushi, which represents the unbalance of the opponent via a combination of displacement, pulling and pushing actions using the grip on the opponents sleeve and lapel; (b) tsukuri, which represents the technique execution and demands a specific combination of legs, trunk and arms positioning to create leverage to throw the opponent in the most efficient way; (c) kake, which represents the finalization of the technique and is characterized by the end of the throwing process (i.e., the phase when the opponent loses contact with the ground up to the impact on his/her back).